DYNAMICS OF SOCIAL INTERACTION IN LEARNING ISLAMIC RELIGIOUS EDUCATION BASED ON SOCIO-CULTURAL THEORY AT SMA NEGERI 1 RANTAU BAYUR BANYUASIN - Fitriyanti Fitriyanti; Leni Misdiyanti; Yelna Septiana; Kasinyo Harto; Irja Putra Pratama (LP2M IAI Al-Khairat Pamekasan, 2026)
This study aims to analyze the dynamics of social interaction in Islamic Religious Education (PAI) learning based on socio-cultural theory at SMA Negeri 1 Rantau Bayur Banyuasin. The focus of this research is to explore how Islamic education teachers act as mediators in shaping religious social interactions that reflect the cultural context of the school environment. This research employs a descriptive qualitative approach, using observation, in-depth interviews, and documentation as data collection techniques. The participants consist of Islamic education teachers, students, and the school principal, selected through purposive sampling. Data were analyzed using the Miles and Huberman interactive model, which includes data reduction, data display, and conclusion verification. The findings reveal that PAI learning at SMA Negeri 1 Rantau Bayur is deeply rooted in local social and cultural values such as mutual cooperation, tolerance, and social awareness. Islamic education teachers play a crucial role as facilitators who integrate Islamic values into students’ daily lives through interactive and collaborative learning. These social interactions not only enhance students’ religious understanding but also strengthen their moral and social character. The implication of this study emphasizes the importance of applying socio-cultural theory in Islamic education to create a collaborative, contextual, and transformative learning environment. The unique value of this research lies in its contribution to enriching the discourse on socially grounded models of religious education in secondary schools.